Usage of joint vibration analysis (JVA) for temporomandibular joint diagnosis at special needs patients - Husseini, Mhd Nawzat (My University, 2019)
Özel Bakım Gerektiren Çocuklarda Temporomandibular Eklem Tanısı için Eklem Titreşim Analizi KullanımıMhd Nawzat HuusseiniProf. Dr. İlknur TanboğaPedodonti Amaç: Bu çalışmanın amacı sporcularda eklem vibrasyon analizini (JVA) kullanmak, temporomandibular eklemi gözlemlemek ve mental rotardasyon, down sendromlu ve otistik sporcular arasında değerleri karşılaştırmaktır Materyal va Metot: Muğla Sıtkı Koçman Üniversitesinde, Türkiye Özel Olimpiyatlar, Spor Etkınliklerin Katılan Özel Gereksinimli Bireylerde, 10-25 yaş arası 100 katılımcı (58 erkek-42 kadın) sağlandi. Bu kesitsel çalışma için hastalar 3 gruba ayrıldı: grup I, zihinsel engelli çocuklar (n = 58): grup II, down sendromu (n = 20) ve grup III, otizm (n = 22). Veri toplama, diş çürüğünün klinik muayenesi, Fonseca’ın anketi, eklem titreşim analizi yapıldı. Tüm veriler istatistiksel olarak değerlendirildi (p≤ 0.05). İstatistiksel Analiz SPSS istatistik yazılımı kullanılarak yapıldı.Bulgular: Elde edilen sonuçlara göre sağ ve sol eklem arasında istatistiksel olarak anlamlı fark vardı. Ancak, JVA'nın cinsiyete göre parametreler arasında istatistiksel olarak anlamlı bir fark yoktu. Sonuç: Araştırmamıza göre, JVA TMJ hastalıklarının erken teşhisi için, özellikle de özel ihtiyaçları olan insanlarda en iyi cihazlardan biridir. JVA hızlı bir şekilde invazif olmayan ve tekrarlanabilir TME kaydı sunar.

Usage of Joint Vibration Analysis (JVA) For Temporomandibular Joint Diagnosis at special Needs patientsMhd Nawzat HuusseiniProf. Dr. Ilknur TanboğaDepartment of Pediatric Dentistry Aim: The purpose of this study is to use Joint Vibration Analysis JVA on special need athletics to observe Tempomandibular joint and compare the values between mental retardation, down syndrome and autistic athletics. Material and methods: 100 participants (58 males- 42 females) aged between 10-25 were enrolled in, Muğla Sıtkı Kocman University, Turkey special olympics sporting events for special needs individuals, Turkey. For this cross study patients were divided into 3 groups: group I is for mental retardation children (n=58), group II is for down syndrome (n=20), and group III is for autisms (n=22). Data collection was done according to clinical examination of dental caries, Fonseca’s questionnaire, joint vibration analysis. All data are evaluated statistically (p≤ 0.05). Statistical Analysis was performed using SPSS statistical software.Results: In the group of topics we took into account, there was statistically a distinction between the right and left joint. But there was no statistically significant distinction between the gender-based parameters of JVA in all three groups.Conclusion: JVA is one of the best devices for early diagnosis of TMJ illnesses, particularly in people with special needs, according to our research. JVA offers quickly non-invasive and repeatable TMJ registration.
Keywords: Çocuk Diş Hekimliği; Down Sendromu; Down Seyndrom; Jva; Özel Bakim Gerektiren Çocuklar; Pediatric Dentistry; Special Need; Tme; Tmed; Tmj; Tmjd